An Exploration Based on Intrinsic, Extrinsic, and Interpersonal Motivation That Affect Learners' Intention to Participate in an English Reading Contest: From Extensive Reading Perspective. (September 2017) - Liu, I-Fan
Reading is the foundation for learning foreign languages. The cultivation of a reading habit should break free of the limitations of traditional classroom-style education in order to bring about the possibility of lifelong learning. However, foreign language learning in Taiwan has traditionally been oriented toward college entrance exams, causing students to learn exam techniques while ignoring the benefits that can be gained from reading, which can be difficult for inspiring learning motivations in students. To encourage a reading habit in learners through extensive reading, this study provided an online English learning community for students to learn in and an online English contest for students to participate in. This study also proposed a hypothetical model to not only examine the relationships between the factors of participative motivation in contests but also predict the intention of learners to participate again in future contests. A total of 361 high school students participated in this study. Through data analysis, our model was shown to achieve good fit, and all hypotheses were supported. Finally, we identify and discuss the phenomena from the relationships in the educational setting.